2020
DOI: 10.1108/jhtt-11-2019-0138
|View full text |Cite
|
Sign up to set email alerts
|

Data breaches in hospitality: is the industry different?

Abstract: Purpose The purpose of this study is to expand on the existing literature by specifically examining data security incidents within the hospitality industry, assessing origins and causes, comparing breaches within the industry with those of other industries and identifying areas of concern. Design/methodology/approach A sample of data breach incidents is drawn from the Verizon VERIS Community Database (VCDB). Statistical comparisons between hospitality and non-hospitality industry firms are conducted followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Another aspect to be highlighted is that in the total cyberattacks that occurred in the period examined, hackers or cybercriminals illegally accessed payment transactions and users' credit card numbers in 22 cyberattacks, especially in data breach attacks. These data confirm the previous findings of Gwebu and Barrows [112] and Wang et al [113], which revealed that data breaches are becoming more common and publicised in travel and hospitality sectors [114]. For instance, a data breach in a marketing company that manages the advertising, promotion, and marketing practices of McDonald's, Coca-Cola, Shell, Asus, hotels, and OTAs' websites had dire consequences not only for the firms involved but also for users' privacy.…”
Section: Cyberattack Incidents In the Travel And Hospitality Industriessupporting
confidence: 93%
“…Another aspect to be highlighted is that in the total cyberattacks that occurred in the period examined, hackers or cybercriminals illegally accessed payment transactions and users' credit card numbers in 22 cyberattacks, especially in data breach attacks. These data confirm the previous findings of Gwebu and Barrows [112] and Wang et al [113], which revealed that data breaches are becoming more common and publicised in travel and hospitality sectors [114]. For instance, a data breach in a marketing company that manages the advertising, promotion, and marketing practices of McDonald's, Coca-Cola, Shell, Asus, hotels, and OTAs' websites had dire consequences not only for the firms involved but also for users' privacy.…”
Section: Cyberattack Incidents In the Travel And Hospitality Industriessupporting
confidence: 93%
“…The increase in demand for information from all parties (hotel brands, their customers and stakeholders) has drawn attention and raised concerns about security, as noted by many of the scientific studies we reviewed (Arcuri et al, 2020;Gwebu & Barrows, 2020;Ncubukezi, 2022) The digital dependency created by online communications facilitates attackers to exploit vulnerabilities in every sector (Kalamkar & Prasad, 2022), including the operation of hotel brands. Therefore, the determinant of the cyber security of a hotel brand is its internal business processes and communication platforms.…”
Section: Security Of the Hotel Product Sales Systemmentioning
confidence: 99%
“…Data breaches could lead to the misuse of personal data for various evil purposes including fraud, theft, bank account break-ins, unsolicited promotion of products and privacy violations (Gashami et al , 2019; Gwebu and Barrows, 2020; Holtfreter and Harrington, 2015; Schatz and Bashroush, 2016). One of the examples of the case is the one that occurred on October 5, 2020.…”
Section: Introductionmentioning
confidence: 99%